ANALISIS FUNGSI KEPEMIMPINAN CAMAT KUBU KABUPATEN ROKAN HILIR - ", Aldi; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Camat leadership is someone ability in takes a decision and opinion and get to beimplementation and smooths accomplishment aim of organization. The purpose of thisresearch is to know Camat leadership in carry out his function in Kubu subdiscrit Regency ofRokan Hilir. To know factor that becomes constraint in camat's leadership in carry out herfungtion in Kubu subdiscrit Regency of Rokan Hilir.In this research, Based on theory which interposed by Sondang P. Siagian (2010: 31)that: Chairman as a determiner that will pass in intent accomplishment purpose, chairman asrepresentative and organization spokesman in connection with another organizations,effective communicator, good mediator, effective integrator, rational, objektif and neutral.The research was conducted at subdiscrit of Kubu and the sample of this research is 26person. In the collecting data, the writer used observation, interview and study ofbibliography. This research included in descriptive research.This result of this research are , the fungtion of Camat leadership on subdiscrit of kubu,Regency of Rokan Hilir that is categories not good, because in the implementation and thefunction not able optimum. It was caused by decrease coordination camat in theimplementation his function. One of factor which identifies the resistor camat leadership isfacility, decrease of connection with another organizations, interaction with society,communication, and conflict intervention.Key word: Function, Leadership and Camat